Estudo comparativo entre a utilização dos concretos convencional e leve nos elementos horizontais das estruturas de edifícios - Marcio Dario da Silva (2003)
This dissertation presents the results of a comparative study between the use of normal and lightweight concrete in the horizontal structural elements of buildings. In all cases the columns are of normal weight concrete. Structural behavior and material consumption are compared based on the results of the analysis and design of a 15-story high residential building. Two different structural models were analyzed. In the first one, frames, having approximately the same stiffness, are used. In the other model large size columns are used in the frames located in the elevator shaft and the staircase. The lightweight reinforced concrete had a specific weight of 17,4 kN/m3 and a characteristic compressive strength of 20 MPa. The design of the lightweight concrete elements wasperformed according to EUROCODE 2 (1999), ACI 213 (1999) and ACI 318 (1999), since there are no specific codes in Brazil for the design of lightweight concrete. TQS reinforced concrete analysis and design software version 7.0 was used. The results of each structural model indicate slightly large lateral displacements for the buildings withlightweight concrete in the slabs and beams. However, the model with large size columns and lightweight concrete and the model with normal concrete and frames of the same stiffness exhibit equal lateral displacements. In all cases, the amount of the necessary reinforcement and the foundations loads were significantly less in structureswith lightweight concrete in the slabs and beams.